A review of sodium receiver technologies for central receiver solar power plants. (December 2015) - Coventry, J.; Andraka, C.; Pye, J.; Blanco, M.; Fisher, J.
Highlights: We examine performance of sodium receivers for central receiver solar power plants. We review past sodium receiver experiments, at Sandia and PSA in the 1980s. We discuss some current development activities in the area of sodium receivers. We discuss liquid–vapour phase change (latent) sodium receivers. We discuss lessons learnt from the nuclear industry with liquid sodium systems. Abstract: This paper examines the potential of sodium receivers to increase the overall solar-to-electricity efficiency of central receiver solar power plants, also known as solar tower systems. It re-visits some of the key outcomes and conclusions from past sodium receiver experiments, in particular those at Sandia National Laboratories and Plataforma Solar de Almeria in the 1980s, and discusses some current development activities in the area. It also discusses research in sodium receivers with a liquid–vapour phase change (heat pipes and pool boilers), to explore whether technologies developed for dish-Stirling systems have applicability for solar tower systems. Lessons learnt from experience in the nuclear industry with liquid sodium systems are discussed in the context of safety risks.